Physiological changes associated with antioxidant enzymes in response to sugarcane tolerance to water deficit and rehydration - Santos, Claudiana Moura dos [UNESP]; Silva, Marcelo de Almeida [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Bortolheiro, Fernanda Pacheco de Almeida Prado [UNESP]; Brunelli, Marcela Cristina [UNESP]; Holanda, Lucas Almeidade [UNESP]; Oliver, Rodrigo [UNESP] (Springer Nature, 2014)
Water deficit is the main limiting factor for sugarcane yield worldwide. Under this stress, the crop develops adaptive mechanisms that participate in maintaining the plants’ water status. A better understanding of these mechanisms may contribute to differentiating tolerant cultivars to be used in genetic improvement programs. Therefore, this study aimed to assess the physiological responses of sugarcane cultivars subjected to water deficit and rehydration. Cultivars RB92579, SP81-3250, SP83-2847 and IAC91-5155 were grown in pots in a greenhouse. These plants were physiologically and biochemically evaluated at three intervals: 0 (before stress), 15 (water deficit) and 27 days (rehydration) after the onset of treatment (DAT) at 85 days after planting. Cultivars RB92579 and SP81-3250 had greater reductions in stem height, number of green leaves, leaf area, relative water content, leaf water potential (Ψw), leaf temperature, stomatal conductance (gs), maximum photochemical efficiency of photosystem II (Fv/Fm), SPAD index and photosynthetic pigments, and inhibited catalase enzyme activity when subjected to water stress. Furthermore, SP81-3250 showed no recovery after rehydration. Water deficit also increased the levels of proline and the enzymes superoxide dismutase and ascorbate peroxidase in all cultivars. We also found increased carbohydrates under stress, except in the cultivar SP81-3250, which had a reduced content. Due to the minor damage caused by drought in the physiology and biochemistry of cultivars SP83-2847 and IAC91-5155, they have higher potential for tolerance and can acclimate to drought. Consequently, oxidative stress can be largely avoided in the chloroplasts of these cultivars by maintaining the balance of antioxidant enzyme activity, photosynthetic efficiency, stomatal control and water status.
Keywords: Saccharum spp.; Drought; Stomatal conductance; Photosynthetic pigments; Oxidative stress